(untitled) (Revista Lusófona de Educação, 2025)
Decree-Law 54/2018 of 6 July opened the application of measures to support learning and inclusion, promoting equal opportunities and social equity, to vocational schools. However, and considering the specificities of vocational education, both in terms of students and the functioning of its subjects, the application of the regulations has been a challenge for teachers/trainers in these schools. In this sense, this quantitative study seeks to understand the perception of teachers/trainers regarding the application of DL 54/2018 in vocational schools, outlining the following objectives: to know the real difficulties experienced by teachers in applying the law; to understand whether, from the point of view of teachers/trainers in vocational schools, this regulation is appropriate to the reality of vocational education, taking into account certification at the end of the course; and to know what the current challenges are for inclusive education in vocational schools. The results point to the need to provide schools with human resources capable of helping teachers to apply the measures; the respondents recognise the need for more training in the area and point out that the regulations are unsuited to the reality of this type of education, which confers professional certification. Keywords: Inclusion; vocational education; professional certification; teachers and trainers